MAP1S controls microtubule stability throughout the cell cycle in human cells - Tegha Dunghu, Justus; Bausch, Elena; Ellenberg, Jan; Gruss, Oliver (Journal of cell science, 2014)
Understanding the molecular basis for proper cell division requires a detailed functional analysis of microtubule (MT)-associated proteins. MT-associated protein 1S (MAP1S), the most ubiquitously expressed MAP1 family member, is required for accurate cell division. Here, using quantitative analysis of MT plus-end tracking, we show that MAP1S knockdown alters MT dynamics throughout the cell cycle. Surprisingly, MAP1S downregulation results in faster growing, yet short-lived, MTs in all cell cycle stages and in a global loss of MT acetylation. These aberrations correlate with severe defects in the final stages of cell division. In monopolar cytokinesis assays, we demonstrate that MAP1S guides MT-dependent initiation of cytokinesis. Our data underline the key role of MAP1S as a global regulator of MT stability and demonstrate a new primary function of MAP1S to regulate MT dynamics at the onset of cytokinesis.